2018
DOI: 10.3389/fimmu.2018.01159
|View full text |Cite
|
Sign up to set email alerts
|

Human P2Y11 Expression Level Affects Human P2X7 Receptor-Mediated Cell Death

Abstract: Adenosine triphosphate (ATP) is known to induce cell death in T lymphocytes at high extracellular concentrations. CD4+ and CD8+ T lymphocytes have a differential response to ATP, which in mice is due to differences in the P2X7 receptor expression levels. By contrast, we observed that the difference in human CD4+ and CD8+ T lymphocyte response toward the synthetic ATP-analog BzATP is not explained by a difference in human P2X7 receptor expression. Rather, the BzATP-induced human P2X7 receptor response in naïve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…In earlier studies, P2Y 11 receptor involvement was suggested through detection of P2Y 11 receptor-encoding mRNA, by exclusion of other possible ATP receptors, and later by siRNA knockdown of the receptor to support pharmacological data, often related to cell survival and cytokine production as well as cell migration and differentiation (711). Functional P2Y 11 receptor expression has been reported in innate immune cells (1, 2) such as dendritic cells (DCs) (8, 9) and macrophages (12) as well as in adaptive immune cells (7, 13), strongly supporting its relevance in immune regulation.…”
Section: Introductionmentioning
confidence: 92%
“…In earlier studies, P2Y 11 receptor involvement was suggested through detection of P2Y 11 receptor-encoding mRNA, by exclusion of other possible ATP receptors, and later by siRNA knockdown of the receptor to support pharmacological data, often related to cell survival and cytokine production as well as cell migration and differentiation (711). Functional P2Y 11 receptor expression has been reported in innate immune cells (1, 2) such as dendritic cells (DCs) (8, 9) and macrophages (12) as well as in adaptive immune cells (7, 13), strongly supporting its relevance in immune regulation.…”
Section: Introductionmentioning
confidence: 92%
“…Human T cells express A2a, A2b, A3, P2X1, P2X4, P2X5, and P2X7, as well as all eight P2Y receptor subtypes ( 34 36 ). P2X1, P2X4, P2Y11, and P2X7 receptors have particularly important roles in the regulation of CD4 T cells ( 10 12 , 36 40 ). Among these receptors, P2X1 receptors are most sensitive with an EC 50 value of 50-1000 nM ATP ( 22 , 41 ).…”
Section: P2x1 Receptors Maintain Mitochondrial Metabolism Of Quiescenmentioning
confidence: 99%
“…According to the current view, P2Y 11 receptors sense extracellular ATP and translate this prototypical danger signal into cytoprotective and immunomodulatory responses (Kennedy, 2017;Vitiello et al, 2012). Expression of P2Y 11 receptors has been detected in immune (Dreisig et al, 2018;Marteau et al, 2005) and non-immune cells (Benoist et al, 2019;Lefort et al, 2018), including cancer cells (Khalid et al, 2017). Among immune cells, P2Y 11 receptors may preferentially be expressed in cells of myeloid origin such as dendritic cells (Schnurr et al, 2003;Wilkin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%